«Un passo davanti»: Vulnerabilità, violenza di genere, responsabilità e conquiste - Fattori, Gabriele (Annali di studi religiosi, 2020)
The truth is that too often it was the law that was responsible if not the moral instigator of much of the gender violence. Everywhere in the world, violence against women is fed by the stereotypes which, generation after generation, perpetuate the idea that a woman should stay ‘a step behind a man’. Incredibly, and in Italy perhaps more than any other place, legislators and judges have been accomplices of those ste-reotypes. Norms and sentences have justified the culture of female subordination and at times seconded violence against ‘disobedient’ women. In 2006 the first set of data published by ISTAT on gender violence in Italy was a real shock for the country. Millions of women had suffered physical or sexual violence. No-one, in the third millennium, could ever have imagined it. That investigation was also a point of no return for the Italian law. Before then the law was co-responsible for a cultural and educative model which instead of fighting against gender crimes, covered them or minimalized them. A new collective consciousness of the phenomenon and the example of International and European rights, in short time, led to the Italian legislation making significant break-throughs in the prevention and repression of violence against women.